VD_FINDINFO Décision / 2013 / 621 vom 5. Juli 2013 - VD Tribunal cantonal (2013)
LÉSION CORPORELLE PAR NÉGLIGENCE, PRESCRIPTION, ACTION PÉNALE | 125 CP, 97 al. 1 CP, 98 CP, 310 CPP (CH), 393 al. 1 let. a CPP (CH)